KONSEP AL-QUR’AN DALAM MENDIDIK EMOTIOANAL QUOTIENT (EQ) - Nurhapipah; Azmiyah; Hafizhatur Rahmah; Afnibar; Ulfatmi (PT. Banjarese Pacific Indonesia, 2023)
Experts in distributing Emotioanal quotient contained in humans through various studies and research. but it turns out that the Qur'an has already discussed emotions which basically emotions can lead to good things as well as bad. If the intelligence tends to have badness, it will be disastrous for human life, so it can be seen that human control is very important and very necessary for humans. In the midst of the hustle and bustle of emotional and psychological problems that do not escape the process of transferring knowledge in the realm of education which can affect the crisis of exemplary as a figure in terms of education, the Qur'an, will be felt to be a solution that is able to provide one-one solution in the world of education today. This type of research is a library study (library research) analysing the interpretation of the Qur'an related to verses about emotions and psychology in educating children. Furthermore, in obtaining data carried out by investigating various literature earlier using the content analysis method, this study concludes that the internalisation of al-Qur'anic values on emotioanal quotient and psychology can produce al-insan al-kamil conditions, that one way to deal with the test is to manage the emotions of patience (Patience), shukr (Gratitude), Taubah (Repentance), Khusnul Khuluq (Good Character), Muraqabah (Self Awareness), Tawakkul (Trust in Allah), Istighfar (Seeking Forgiveness).